PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN BRAIN BASED LEARNING PADA MATERI SISITEM PERSAMAAN LINEAR DUA VARIABEL DI KELAS VIII SMP - Yullia Rahma Fitri (Departemen Matematika, 2021)
The purpose of this research is to design student worksheets (LKPD) Brain Based Learning valid and practical on SPLDV material for class VIII SMP . This research is a developmental research using the Plomp model. Plom’s model of 3 stages: the preliminary stage, prototyping stage and evaluation stage. Based on the results of data analysis seen from the aspects of the feasibility of content, language, presentation and graphics, the validity level of 86.72% was obtained with a very valid category. Meanwhile, at the level of practicality of the LKPD obtained from the student response questionnaire, the practicality was 89.43% in the very practical category. Based on the results obtained, it can be concluded that the LKPD based on the brain based learning model for SPDV material in class VIII SMP can be declared valid and practical. Keywords – development Research, Student Worksheet, Brain Based Learning